2017 IEEE International Conference on Communications (ICC) 2017
DOI: 10.1109/icc.2017.7996381
|View full text |Cite
|
Sign up to set email alerts
|

2D time-frequency interference modelling using stochastic geometry for performance evaluation in Low-Power Wide-Area Networks

Abstract: Abstract-In wireless networks, interferences between transmissions are modelled either in time or frequency domain. In this article, we jointly analyze interferences in the timefrequency domain using a stochastic geometry model assuming the total time-frequency resources to be a two-dimensional plane and transmissions from Internet of Things (IoT) devices timefrequency patterns on this plane. To evaluate the interference, we quantify the overlap between the information packets: provided that the overlap is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 20 publications
0
56
0
1
Order By: Relevance
“…To obtain more general results, [11] uses a stochastic geometry model to jointly analyze interference in the time and frequency domains. It is observed that when implementing a packet repetition strategy, i.e., transmitting each message multiple times, the failure probability reduces, but clearly the average throughput decreases because of the introduced redundancy.…”
Section: Related Workmentioning
confidence: 99%
“…To obtain more general results, [11] uses a stochastic geometry model to jointly analyze interference in the time and frequency domains. It is observed that when implementing a packet repetition strategy, i.e., transmitting each message multiple times, the failure probability reduces, but clearly the average throughput decreases because of the introduced redundancy.…”
Section: Related Workmentioning
confidence: 99%
“…In [13], a novel receiver for grantfree radio access IoT networks has been designed, which benefits from oscillator imperfection of cheap IoT devices for contention resolution. In [15], outage probability in grantfree access has been studied by assuming a constant received power from all contending devices, which is not the case in practice regarding the limited transmit-power of IoT devices, as well as lack of channel state information at the deviceside for power control. The success probability in grant-free radio access has been also analyzed in [8,16] by assuming a Poisson point process (PPP) distribution of IoT devices.…”
Section: A Literature Studymentioning
confidence: 99%
“…From the battery lifetime analysis in (15), one sees that battery lifetime of devices may decrease in n i and P i because of the potential increase in the energy consumption per reporting period. Furthermore, when reliability of communication is lower than a threshold, increase in n i and P i may decrease the need for listening to the channel for ACK arrival and retransmissions, and hence, increasing n i and P i may increase the battery lifetime.…”
Section: Optimized Operation Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of LoRa networks, a mathematical analysis on the uplink coverage is conducted in [9] via stochastic geometry, which yet considers only the strongest interferer and ignores the time dependence of (partially) overlapping packets. Recent works in [10] and [11] consider channel fading, aggregate interference, and accurate packet overlapping, and yet it is difficult to obtain the exact distribution of packet success probability analytically. In summary, a tractable and accurate analytical model is highly needed for the performance evaluation in LoRa networks, which also facilitates further system optimization with low-complexity and low-overhead design.…”
Section: Introductionmentioning
confidence: 99%